Augmented Reality as a Promoter of Visualization for the Learning of Mathematics in Ninth-Year of Basic Education - Espinosa-Pinos, Carlos (2023)
This research focused on developing a mobile application in Meta-verse augmented reality to improve the learning of notable products, factoring, and linear equations in ninth-grade students of the intercultural bilingual educational unit of the millennium “Pueblo Kisapincha” based on the notional method. The methodology applied was quasi-experimental and longitudinal, where related samples were compared using a diagnostic test versus a subsequent evaluation of knowledge. The sampling technique was by non-probabilistic convenience comprising 25 students and 15 teachers to whom a structured questionnaire was applied to determine the predisposition to work in the classroom with augmented reality, which was validated with Cronbach's alpha statistic (α = 0.844). The students’ scores improved significantly after participating in both evaluations, with the post-evaluation being the one that showed the highest score according to the Bayesian T-test applied to related samples. A proposal of activities was designed to motivate the study of algebraic expressions; this product was implemented considering the ADDIE instructional model, guiding each movement with its respective resolution process as a form of feedback. The proposal was evaluated by two experts in technology and two experts in education with more than ten years of experience. In conclusion, developing an augmented reality mobile application in Metaverse to improve the learning of introductory algebra proved to be a valuable and effective tool to contribute to student learning. The mobile application provided an interactive and engaging learning experience, so it is recommended to incorporate this mobile application in the curriculum of the Kisapincha educational unit and its possible implementation in other similar educational institutions.